Disclosure of Financial Information via the Internet by the Portuguese Local Authorities - Helena Mendes; Carlos Santos; Augusta Ferreira; Azevedo, G.; Oliveira, J. (Tools, Strategies and Practices for Modern and Accountable Public Sector Management, 2019)
In the context of new public management, public administration must be alert to the increasing needs of citizens, providing public organizations with efficient management systems in order to rationalize the financial resources and disseminate transparent and accurate economic and financial information to further assess the organizational performance. There have been recent technological advances, namely the use of the internet, that have influenced the way financial information is accessed. This work aims to assess the level of disclosure of financial information on the websites of local authorities in Portugal and the identification of possible factors that may influence the level of disclosure. Given the results in this study, it is time-consuming and difficult to find financial information on the websites. This hinders the users in their assessment on where and how mayors apply public resources. Among the factors tested, the size and political competition are the ones that seem to influence the level of disclosure of financial information on the website.